Ethnic differences in incidence of sudden infant death syndrome in Birmingham. Issue 8 (August 1990) - Kyle, D; Sunderland, R; Stonehouse, M; Cummins, C; Ross, O
Abstract : Among the 45, 204 live births in Birmingham in the three calendar years 1981-3, there were 218 postneonatal deaths, giving a postneonatal mortality rate of 4.82 per 1000 live births. Postneonatal mortality rates were 4.22 for whites, 5.91 for Asians (relative risk 1.26, 95% confidence interval (CI) 1.04 to 1.53) and 8.20 for Afro-Caribbeans (relative risk 1.78, 95% CI 1.25 to 2.55). Among Asians malformations were common (3.36) and sudden infant death syndrome rare (1.18), in contrast to Afro-Caribbeans among whom the rates were 0.66 and 5.25, respectively. Logistic regression analysis demonstrated a significantly lower risk of sudden infant death syndrome (SIDS) in Asians and significantly raised risks of SIDS in very low birthweight babies and those with unemployed parent(s). Ethnic differences persisted after controlling for maternal age, social class, and birth weight. Studies of sociocultural differences in child rearing practices are needed and may uncover important aetiological factors of sudden infant death syndrome.